2013
DOI: 10.1161/strokeaha.112.672303
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K Antagonists–Associated Cerebral Hemorrhages

Abstract: Background and Purpose-The high prevalence of atrial fibrillation in aging populations leads to an increasing incidence of vitamin K antagonists-associated intracerebral hemorrhages (VKAs-ICH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 28 publications
(32 reference statements)
3
27
1
Order By: Relevance
“…17,18 In addition, evidence supporting a link between CAA and OAC-ICH includes the demonstration that the APOE e2 allele, a known genetic risk factor of CAA-related lobar ICH, 19,20 is more common in warfarin-associated ICH than in control patients on warfarin without ICH, 8 and that individual cases of ICH following anticoagulation or coronary thrombolysis revealed advanced CAA on autopsy. 21,22 Our findings are in apparent disagreement with those derived from the PITCH study by DequatrePonchelle et al 12 who found no influence of OACs on the anatomical distribution of ICH but a significant effect of these compounds on the volume of deep brain hematomas. This would support the conclusion that deep perforating arteries are more sensitive to anticoagulation than cortical-subcortical vessels.…”
Section: Statistical Analyses Differences Among the Treatment Groupscontrasting
confidence: 99%
See 3 more Smart Citations
“…17,18 In addition, evidence supporting a link between CAA and OAC-ICH includes the demonstration that the APOE e2 allele, a known genetic risk factor of CAA-related lobar ICH, 19,20 is more common in warfarin-associated ICH than in control patients on warfarin without ICH, 8 and that individual cases of ICH following anticoagulation or coronary thrombolysis revealed advanced CAA on autopsy. 21,22 Our findings are in apparent disagreement with those derived from the PITCH study by DequatrePonchelle et al 12 who found no influence of OACs on the anatomical distribution of ICH but a significant effect of these compounds on the volume of deep brain hematomas. This would support the conclusion that deep perforating arteries are more sensitive to anticoagulation than cortical-subcortical vessels.…”
Section: Statistical Analyses Differences Among the Treatment Groupscontrasting
confidence: 99%
“…[7][8][9][10] However, data on the impact of specific small-vessel arteriopathies on OAC-related ICH are scarce, mainly derived from studies including small case series, sometimes recording individual history of OAC use without taking into consideration the intensity of anticoagulation, 7 including patients receiving heparin at the time of stroke, 8,11 or aimed at addressing different issues, 8,9,11 with only a few notable exceptions. 10,12 In this regard, a novel finding from our data is the evidence of a direct dose-response relationship between OAC treatment and lobar ICH, as illustrated by the increasing number of patients in this subgroup as the INR values increase. We speculate that OACs affect CAA and hypertensive arteriolosclerosis equally when INR values are within the therapeutic range, but that they exert a differential impact on the 2 cerebral microangiopathies, with a greater effect on cortical-subcortical vessels, in case of excessive anticoagulation.…”
Section: Statistical Analyses Differences Among the Treatment Groupsmentioning
confidence: 51%
See 2 more Smart Citations
“…Patient registration years ranged from 1993 to 2014, with 90% of patients from 2004 to 2013. Registry methods are summarized in Supplementary Table I, with further details previously published 2, 3, 4, 14, 15, 16, 17, 18, 19, 20…”
Section: Methodsmentioning
confidence: 99%